Bioaccumulation of heavy metals in fish species collected from former tin mining catchment - Ashraf, M.A.; Maah, M.J.; Yusoff, I. (2012)
This study has been carried out to determine the accumulation of heavy metals (arsenic, copper, lead, tin and zinc) in fish samples collected from former tin mining catchment. Total eight types of fish family having fifteen different species are identified. Cyperinidae is the most abundant family with eight different species found in the catchment. Fish samples were analysed by using inductively coupled plasma optical emission spectrophotometer ICP-OES. The accuracy of method is validated by certified reference material. The highest level of arsenic was observed in Hampala macrolepidota while Osteochilus hasselti shows the least. For Copper concentrations, the maximum was obtained in Mastacembelus armatus and the minimum in Oxyeleotris marmorata. High levels of lead, tin and zinc were found in the Rasbora elegans, Trichogaster trichopterus. Oxyeleotris marmorata respectively while Macro brachium resenbergii, Mastacembelus armatus, Rasbora elegans had the least concentrations. The sequence of order of the heavy metals measured was Sn > Pb >Zn > Cu> As, respectively. The results showed elevated levels of tin, led and zinc in all the fish samples although copper and arsenic were available in relatively low concentration in the most samples. Sn, Pb, and Zn concentration in the samples were greater than Malaysia food act permissible levels. Hazard index < 1 suggests unlikely adverse health effects whereas HI > 1 suggests the probability of adverse health effects. Although the heavy metals analysed in the catchment did not pose any immediate health risk to humans but due to the bioaccumulation and magnification of these heavy metals in humans, it is essential to safeguard levels of the metals in the environment.